Religious Based Learning as a Form of Cultivating Character Values in Children with Special Needs at SDLB Jenangan, Ponorogo - Vivi Vellanita Wanda Damayanti; Restiana Irniasari (International Journal of Emerging Issues in Early Childhood Education, 2020)
The application of character education has been carried out in public schools for more than a decade. In character education, the divinity value became the first value that was crucially determined and applied. By pointing the divinity value it is expected that students could understand the values of morality and humanity. Not only in public schools but also in special needs schools, the value of religiosity was applied and is a major cornerstone in the learning process. In this qualitative study the religious values were applied in SDLB Jenangan, Ponorogo, would be discussed in detail. The purpose of this research was to explain the urgency of building the character value in children with special in the learning process. Data in this study were collected using observation, interview, and documentation. The results of this study showed that the learning process carried out in SDLB Jenangan, Ponorogo, represented a religion-based learning system. This religion-based education aimed to make the special need students being able to increase their self-confidence and control. Further, it is expected that the student would have the ability to minimize their attitudes.